33. STUDYING THE MEMORY ENHANCING EFFECT OF HUP A SOFT CAPSULE USING TRIMETHYLTIN CHLORIDE MODEL ON MICE (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the memory enhancing effect of Hup A soft capsules using the Trimethyltin chloride (TMT) model on mice. Method: The product used in the study is Hup A soft capsule that met Enterprise standard, mice were given Hup A at doses of 192mg/kg/24h and 384mg/kg/24h, then injected peritoneal with Trimethyltin chloride (TMT) at 2,4mg/kg/24h. Mice were tested on the Bold Hold and the Automatic Conditioned Reflex machine. Mice were monitored for the following indicators: the total number of times the mouse stuck its head into the hole within 5 minutes and the total number of times the mouse responded to avoid electric shock, and observed mouse brain histopathology. Results: Compared to the TMT group, these Hup A groups increased the number of times these animals stuck their heads into the hole, but there was no difference (p >0.05). However, these Hup A groups increased the number of times these animals avoided electric shock and showed less damage in brain histology than the TMT group. Conclusion: Our study showed that Hup A soft capsules enhance memory by increasing natural exploration activities, reducing anxiety, increasing the ability to avoid electric shock, and reducing brain tissue damage in mice caused by TMT.
Keywords: Hup A, memory enhancement, Trimethyltin chlorid.